2018
DOI: 10.1111/jcmm.14049
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a 4‐mRNA metastasis‐related prognostic signature for patients with breast cancer

Abstract: Metastasis‐related mRNAs have showed great promise as prognostic biomarkers in various types of cancers. Therefore, we attempted to develop a metastasis‐associated gene signature to enhance prognostic prediction of breast cancer (BC) based on gene expression profiling. We firstly screened and identified 56 differentially expressed mRNAs by analysing BC tumour tissues with and without metastasis in the discovery cohort (GSE102484, n = 683). We then found 26 of these differentially expressed genes were associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 32 publications
2
28
0
Order By: Relevance
“…48 Several previous studies have reported prognostic signatures for BC. [49][50][51][52][53][54] Compared with the models, our prognostic model in this article has following advantages. Firstly, our prognostic model was build using several statistical analysis tools to ensure its rigor and accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…48 Several previous studies have reported prognostic signatures for BC. [49][50][51][52][53][54] Compared with the models, our prognostic model in this article has following advantages. Firstly, our prognostic model was build using several statistical analysis tools to ensure its rigor and accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…A 24-mRNA signature model was also constructed for early-relapse prediction of patients with hepatocellular carcinoma, which may help facilitate disease management for individual patients (48). A metastasis-related 4-mRNA gene signature model has been demonstrated to effectively classify patients with breast cancer into high-and low-risk groups (49). In addition, Cui et al (38) developed a 6-mRNA signature model that may potentially improve the risk stratification of patients with head and neck squamous cell carcinoma (50).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we used Cox model analysis to construct a gene signature that includes several genes to enhance prognostic prediction efficiency and sensitivity to TNBC. It has been widely confirmed that combined genetic models are superior to previous single gene markers in disease prediction and diagnoses [32].…”
Section: Discussionmentioning
confidence: 99%